Voluntary Pension System : Challenge of Expanding Coverage - Phuong, Nguyen Thi Thu; Castel, Paulette (World Bank, Washington, DC, 2017)
Since 1947, the Vietnam Social Security (VSS) has provided social insurance to public servants and armed forces personnel in Vietnam. In 1995, the Government merged the social insurance unit of the Ministry of labour, invalids and social affairs with that of the Vietnam General Confederation of labor. At the same time the system became mandatory to the employees of the newly developing private sector. The consolidated system is publicly managed by the VSS administration. VSS collects contributions and pay social insurance benefits (in case of sickness and sick leaves, maternity and family planning related leaves, work injury and professional disease, survivorship and to people that reached pension ages). This paper investigates this issue by reviewing the characteristics of employment in Vietnam. It concludes that the risk that social coverage remains limited for many years is high and, presents accordingly some policy options to augment VSS's chances to reach universal coverage in the future.